2023
DOI: 10.1590/1519-6984.275953
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity and apoptosis-inducing mechanism of Curcuma longa (Turmimax®) on HeLa cell lines

H. M. Firoz,
S. Nanjundaiah,
C. T. Sadashiva
et al.

Abstract: Curcumin, the primary polyphenol found in turmeric, is derived from the Curcuma longa plant. Since curcumin is nontoxic and has a wide range of medicinal qualities, including anti-oxidant, analgesic, anti-inflammatory, and antibacterial action, it has been widely employed in Ayurveda medicine for ages. Curcumin has recently been discovered to have anti-cancer properties through its impact on numerous biological pathways involved in carcinogenesis, metastasis, tumorigenesis, cell cycle regulation, mutagenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Previous studies found that curcumin possesses a variety of pharmacological properties such as anti-tumor, antibacterial, anti-inflammatory and antioxidant effects. 52 , 53 Currently, two clinical trials show results. One of them is a phase II trial using curcumin in patients with advanced pancreatic cancer, which has been completed and the results are available (NCT00094445).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that curcumin possesses a variety of pharmacological properties such as anti-tumor, antibacterial, anti-inflammatory and antioxidant effects. 52 , 53 Currently, two clinical trials show results. One of them is a phase II trial using curcumin in patients with advanced pancreatic cancer, which has been completed and the results are available (NCT00094445).…”
Section: Resultsmentioning
confidence: 99%